2009
DOI: 10.3126/aej.v9i0.2116
|View full text |Cite
|
Sign up to set email alerts
|

Standard Setting on Pesticide Residues to Ensure Food Safety

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…With the increasing threat of pesticide residue and contamination government had taken some initiatives to set maximum residue limit for some agriculture produce. Food Act 1967 and Food Regulation 1970 in Nepal had established and implemented Maximum Residue Limit (MRLs) for pesticides in food products, but that is limited to cereals, pulses and their products, bottled water and infant foods commodities [33,34] [35]. This was supposed to be effective from September 2019.…”
Section: Cereals Fruits Active Ingredient (Kg/ha) Applied Vegetable Cmentioning
confidence: 99%
“…With the increasing threat of pesticide residue and contamination government had taken some initiatives to set maximum residue limit for some agriculture produce. Food Act 1967 and Food Regulation 1970 in Nepal had established and implemented Maximum Residue Limit (MRLs) for pesticides in food products, but that is limited to cereals, pulses and their products, bottled water and infant foods commodities [33,34] [35]. This was supposed to be effective from September 2019.…”
Section: Cereals Fruits Active Ingredient (Kg/ha) Applied Vegetable Cmentioning
confidence: 99%
“…Pesticides, especially the organochlorine (OC) and organophosphate (OP) tend to persist in the environment, causing several types of damages including lowering of biodiversity, soil contamination and water contamination etc. Excessive use of persisting pesticides in the fields also have caused surface and underground water contamination are illustrated by records of some international studies (Giri 1998, Lama 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise Kumari et al (2002Kumari et al ( , 2003 also found the residues of organophosphate and synthetic pyrethroids in addition to organochlorine compounds in seasonal vegetables from Haryana, India. However, considering the pesticide scenario of Nepal, lack of regular monitoring scheme for MRLs on pesticides, has affected the export of tea, honey and other food commodities as well as certification of organic food materials (Lama 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These kinds of safety regulations, particularly concerning chemical pesticides in food in Nepal, is still under development (CBS, 2013). Previous studies have found pesticide residues in vegetables but these studies did not assess the health risks associated with dietary intake of pesticides (Giri et al, 2012;Koirala et al, 2007;Lama, 2008). The dietary intake of pesticides (especially the amount consumed) differs in different age groups which may lead to different levels of exposure to pesticides.…”
Section: Introductionmentioning
confidence: 99%